Coronary vasoconstrictor responses are attenuated in young women as compared with age-matched men - Momen, Afsana (Blackwell Science Inc, 2010)
Recent work in humans suggests coronary vasoconstriction occurs with static handgrip with a time course that suggests a sympathetic constrictor mechanism. These findings are consistent with animal studies that suggest this effect helps maintain transmural myocardial perfusion. It is known that oestrogen can attenuate sympathetic responsiveness, however it is not known if sympathetic constrictor responses vary in men and women. To examine this issue we studied young men (n = 12; 28 ± 1 years) and women (n = 14; 30 ± 1 years). Coronary blood flow velocity (CBV; Duplex Ultrasound), heart rate (ECG) and blood pressure (BP; Finapres) were measured during static handgrip (20 s) at 10% and 70% of maximum voluntary contraction. Measurements were also obtained during graded lower body negative pressure (LBNP; activates baroreflex-mediated sympathetic system) and the cold pressor test (CPT; a non-specific sympathetic stimulus). A coronary vascular resistance index (CVR) was calculated as diastolic BP/CBV. Increases in CVR with handgrip were greater in men vs. women (1.25 ± 0.49 vs. 0.26 ± 0.38 units; P < 0.04) and CBV tended to fall in men but not in women (−0.9 ± 0.9 vs. 1.7 ± 0.8 cm s(−1); P < 0.01). Changes in CBV with handgrip were linked to the myocardial oxygen consumption in women but not in men. CBV reductions were greater in men vs. women during graded LBNP (P < 0.04). Men and women had similar coronary responses to CPT (P = n.s.). We conclude that coronary vasoconstrictor tone is greater in men than women during static handgrip and LBNP.